2014
DOI: 10.1080/02640414.2014.964749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of repeated sprints on postprandial endothelial function and triacylglycerol concentrations in adolescent boys

Abstract: This study investigated if repeated, very short duration sprints influenced endothelial function (indicated by flow-mediated dilation) and triacylglycerol concentrations following the ingestion of high-fat meals in adolescent boys. Nine adolescent boys completed two, 2-day main trials (control and exercise), in a counter-balanced, crossover design. Participants were inactive on day 1 of the control trial but completed 40 x 6 s maximal cycle sprints on day 1 of the exercise trial. On day 2 capillary blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 47 publications
6
31
1
1
Order By: Relevance
“…For the first time in adolescents, we provide evidence that a single bout of MIE performed one hour before a HFM may preserve endothelial function, and that an equivalent bout of HIIE not only prevents this attenuation but improves endothelial function despite no reduction in plasma [triacylglycerol]. Whilst the benefits of prior moderate-intensity (54) and sprint interval (53) exercise on postprandial macrovascular function have been shown to be unrelated to changes in plasma [triacylglycerol] in adolescents, we are the first to identify an independent effect of exercise intensity. Our findings concur with those reported by Tyldum et al (70), however these authors identified that this protective effect of exercise performed the day before a HFM was related to an exercise-induced increase in antioxidant capacity, which we did not observe in this study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For the first time in adolescents, we provide evidence that a single bout of MIE performed one hour before a HFM may preserve endothelial function, and that an equivalent bout of HIIE not only prevents this attenuation but improves endothelial function despite no reduction in plasma [triacylglycerol]. Whilst the benefits of prior moderate-intensity (54) and sprint interval (53) exercise on postprandial macrovascular function have been shown to be unrelated to changes in plasma [triacylglycerol] in adolescents, we are the first to identify an independent effect of exercise intensity. Our findings concur with those reported by Tyldum et al (70), however these authors identified that this protective effect of exercise performed the day before a HFM was related to an exercise-induced increase in antioxidant capacity, which we did not observe in this study.…”
Section: Discussionmentioning
confidence: 78%
“…In children, cross-sectional evidence suggests that high-intensity exercise may have a positive effect on fasting vascular function (32). Additionally, a single bout of moderate-intensity exercise (54) and sprint interval exercise (53) has been shown to preserve postprandial macrovascular function the following day in adolescent boys. However, the total exercise stimulus in these two studies was not equivalent, and the authors did not include a measure of microvascular function.…”
Section: Introductionmentioning
confidence: 99%
“…Both interval exercise at 85%-90% and continuous exercise at 60% of maximum oxygen uptake (VO 2max ) have been shown to be effective at attenuating these figures, even when the session is conducted the previous day, which indicates that physical exercise has a prolonged and late effect as a cardioprotective agent. 15,[22][23][24]30 Resistance training exhibits the same behavior in relation to attenuation of endothelial dysfunction. 25,31 Therefore, in contrast with the effects of physical exercise on the parameters of oxidative stress associated with eating an HFM, attenuation of endothelial dysfunction appears to be more strongly linked to performing physical exercise than to the type, duration or intensity of exercise session, or other factors, such as study population.…”
Section: Effects On Endothelial Function Of Physical Exercise Associamentioning
confidence: 89%
“…However, the methodologies for assessment of endothelial function are still highly varied, and there is no consensus in the literature on the most appropriate for measuring vasodilation derived from the endothelium. The most widely used techniques include flow-mediated dilation (FMD) and/or brachial artery dilation (BAD) 22,28,30,66 and pulse wave velocity (PWV), 23,24,31 and it is also possible to assess Acetylcholine Response. 15 After eating an HFM, the values of FMD and PWV tend to drop significantly from 2 h to 4 h postprandially, [22][23][24] and a reduction in endothelial function can be detected up to 6h30 30 afterwards.…”
Section: Effects On Endothelial Function Of Physical Exercise Associamentioning
confidence: 99%
See 1 more Smart Citation